Model Numeris Untuk Menghitung Kebutuhan Air Irigasi - Arafat, Muhammad; Mudjiatko, Mudjiatko; Hendri, Andy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Analysis of irrigation water requirements by using a manual analysis model will make calculations longer, repetitive simulations and calculations will require high accuracy and require a relatively long time. We need the fastmodel, the fastmodel is a numerical model where repetitive calculations and repetitive simulations will be faster. What is the numerical model for calculating the needs of irrigation water with a variety of patterns and optimal planting time that is valid in solving the problem of need for comprehensive irrigation water. Result of rain data calculation was validated with several tests, by testing Outlier Test, Calculation of Effective Rainfall, Calculation of Evapotranspiration, and water requirements. It was found that numerical model for calculating the needs of irrigation water with validation and obtained results that were not much different. Optimal irrigation water requirements which use a small amount of channel water.Keywords : analysis of irrigation water needs, numerical models, calculation validation